TINJAUAN YURIDIS PELAKSANAAN REHABILITASI BAGI PENYALAH GUNA NARKOTIKA BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Mitarji; Indah Sari (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2025)
This study aims to explain: About the Legal Review of the Implementation of Rehabilitation for Narcotics Abusers Based on Law Number 35 of 2009 concerning Narcotics, as a positive law in Indonesia in efforts to overcome and rehabilitate narcotics abusers. In Article 54 of Law Number 35 of 2009 concerning Narcotics it is explained that: "narcotics addicts and victims of narcotics abuse are required to undergo medical rehabilitation and social rehabilitation." In addition, the Supreme Court has also issued a Circular Letter of the Supreme Court (SEMA) Number 4 of 2010 concerning the Placement of Victims of Narcotics Abuse and Addicts into Medical Rehabilitation and Social Rehabilitation Institutions. However, there are still many victims and narcotics addicts who are sentenced to prison, not rehabilitation by the court. This study uses normative juridical legal research and a document or literature study method by reviewing laws and regulations, books, and journals related to the title of this thesis. The results of this study indicate that perpetrators of drug abuse for personal use are sentenced to rehabilitation. This is in accordance with Law Number 35 of 2009 concerning Narcotics and Supreme Court Circular Letter (SEMA) Number 4 of 2010.